The impact of early vs. delayed surgery on outcomes in cervical spinal cord injury without fracture or dislocation - Xiao, Sirui; Yan, Hui; Bao, Beixi; Wu, Yuxuan; Cheng, Xiaokang; Xu, Chunyang; Tang, Jiaguang (Frontiers in Surgery, 2025)
ObjectiveThis study aims to retrospectively analyze 104 patients diagnosed with cervical spinal cord injury without fracture or dislocation (CSCIwoFD) who underwent surgical treatment, in order to compare the effects of early vs. delayed surgical intervention on neurological functional recovery.MethodsPatients diagnosed with CSCIwoFD and treated surgically at our institution between August 2020 and January 2023 were retrospectively reviewed. Based on the time interval from injury to surgery, patients were categorized into two groups: early surgery group (Group A) and delayed surgery group (Group B). Neurological function was assessed using the Japanese Orthopaedic Association (JOA) score, the American Spinal Injury Association motor score (AMS), and sensory score (ASS). Improvement rates were calculated as the JOA recovery rate (RR), AMS recovery rate (AMSRR), and ASS recovery rate (ASSRR). Pearson correlation analyses were performed using R software to determine the linear relationships between postoperative neurological outcomes and imaging parameters, including maximum canal compromise (MCC), maximum spinal cord compression (MSCC), developmental spinal canal stenosis, and ossification of the posterior longitudinal ligament (OPLL), as well as with postoperative complications. Intergroup comparisons were also made regarding hospitalization duration, time to return to work post-discharge, in-hospital treatment costs, and patient satisfaction 2 years after treatment.ResultsMSCC showed a significant positive correlation with postoperative neurological recovery metrics including RR, JOA, AMS, and AMSRR, while its correlation with ASSRR was weaker. No significant associations were observed between MSCC and patient age, sex, or surgical approach; however, a mild positive correlation with surgical timing was identified. Compared to the delayed surgery group, the early surgery group exhibited longer operative duration, greater intraoperative blood loss, and higher postoperative drainage volume, but there are no significant difference in the incidence of complications (P > 0.05). There were also no significant differences between groups in terms of the number of fused segments, bone fusion rate at 6 months, patient satisfaction at 2 years, length of hospital stay, time to return to work, or hospitalization costs (P > 0.05). Imaging parameters revealed higher MCC and MSCC values in the early surgery group, but only the difference in MSCC reached statistical significance (P < 0.05).Efficacy evaluationAt admission, there were no a significant differences in JOA, AMS, or ASS scores between the groups. Postoperatively, both groups showed improvements in JOA, ASS, and AMS scores, with significantly better outcomes in the early surgery group. Intergroup comparisons at 6 months, 1 year, and 2 years postoperatively showed statistically significant differences in JOA and AMS scores (P < 0.05), and significant differences in ASS scores at 1 and 2 years postoperatively (P < 0.05). Notably, the 2-year postoperative JOA score difference between groups was 2.71 points, exceeding the minimal clinically important difference (MCID) threshold. For recovery rates (RR, ASSRR, AMSRR), statistically significant differences were found between groups at both 1 and 2 years postoperatively (P < 0.05). In the early surgery group, Pearson analysis indicated that MSCC was positively correlated with RR at 3 months (γ = 0.527, P < 0.05) and AMSRR at 3 months (γ = 0.277, P < 0.05).ConclusionBoth early and delayed surgical interventions can improve spinal cord function in patients with CSCIwoFD; however, early surgery is associated with better neurological recovery. Among imaging predictors, MSCC is particularly effective in forecasting motor recovery in early surgery patients. When determining the optimal timing for surgery, clinicians should consider individual comorbidities and the severity of spinal cord injury. Under conditions of stabilized traumatic stress response, surgical intervention within 7 days of injury is recommended to maximize neurological recovery and prognosis.